Implementation Of Health Belief Models In Efforts To Prevent Covid-19 - Sodik, Muhammad Ali; Hera Aviyuni; Mika Vernicia Humairo (Journal of Global Research in Public Health, 2021)
Background: WHO Designated COVID-19 as a health problem with a global emergency status with the highest level of alertness. Coronaviruses are a large family of viruses that cause disease in humans and animals. At the start of the pandemic The total number of COVID-19 cases in Indonesia was 248,852 confirmed. Therefore, the number infected with COVID-19 will continue to grow. Aim: Adherence to preventive health standards and behaviors in the community is very important to better control disease and be able to know preventive health behaviors from COVID-19 based on the Health Belief Model component in the community. Method: This research design uses observational analytic with cross sectional approach. The study was conducted online due to the COVID-19 pandemic. Respondents were collected by accidental sampling by distributing questionnaires in the Kediri community. Multivariariate analysis using the Ordinal Regression Test. Result: This research found that there is an effort of COVID-19 prevention with the Perceived Saverity value =0,00, the Perceived Benefits value =0,004 and the Cues To Action value = 0,000 where as those that have no effect in efforts to prevent COVID-19 are the Perceived Susceptibility value = 0,268, the Perceived Barries value =0,606 and the perception of Self Efficacy value = 0.0684. Conclusion: Can concluded that there an effect of the theory health belief model on efforts to prevent COVID-19. From the results, there are 3 components that influence, Perceived Saverity, Perceived Benefits,Cues To Action. Meanwhile there are 3 components have no effect, Perceived Susceptibility,Perceived Barries, Self Efficacy